Analisis Pergerakan Harga Cabai Merah Di Provinsi Jambi - Adikusuma, Fakta; Ernawati, Ernawati; Yanita, Mirawati (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2022)
This study aims to analyze the price movement of red chili in the producer, wholesaler, and consumer market. The scope of the research area is Jambi Province with a sample of red chili prices in the markets of Jambi City and Bungo Regency, used time series data on the daily price of red chili during the period from June 3, 2019 to June 3, 2020 (263 days). Sources of data obtained from the National PIHPS. This study uses the CV (Coefficient of Variation) analysis method to see price movements. The results of CV analysis show that the highest fluctuation in the price of red chili is at the wholesaler's price, which is 45.46 percent. Meanwhile, in producer prices, price fluctuations tend to be lower than consumer prices with CV values of 40.33 percent and 42.64 percent, respectively. Based on the CV value of red chili prices per monthly period, it shows that the price of red chili wholesalers experienced the highest price fluctuations that occurred in January 2020, with a CV value reaching 38 percent. Likewise for consumer prices, the highest fluctuation occurred in January 2020 which reached 34 percent. This could be due to changes in demand for red chilies in accordance with religious holidays, where January 2020 coincides with the celebration of the new year and after the end of Christmas. This condition indicates that the demand for chili has increased during religious holidays, where this change in demand has not been responded well to the existing supply.